2017
DOI: 10.1007/s00299-017-2115-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals metabolic alteration due to consecutive monoculture and abiotic stress stimuli in Rehamannia glutinosa Libosch

Abstract: We deeply investigated the mechanism underlying metabolic regulation in response to consecutive monoculture (replanting disease) and different abiotic stresses that unfolded the response mechanism to consecutive monoculture problem through RNA-seq analysis. The consecutive monoculture problem (CMP) resulted of complex environmental stresses mediated by multiple factors. Previous studies have noted that multiple stress factors in consecutive monoculture soils or plants severely limited the interpretation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 61 publications
2
10
0
Order By: Relevance
“…This shows that GN121 was weakly affected by Pi deficiency. In a recent study, limonene and pinene degradation was reported as a stress defense mechanism process, which was significantly reinforced under abiotic stress (Tian et al, 2017 ). Only one gene was enriched in this pathway in the present study, and up-regulated under the condition of Pi starvation.…”
Section: Discussionmentioning
confidence: 99%
“…This shows that GN121 was weakly affected by Pi deficiency. In a recent study, limonene and pinene degradation was reported as a stress defense mechanism process, which was significantly reinforced under abiotic stress (Tian et al, 2017 ). Only one gene was enriched in this pathway in the present study, and up-regulated under the condition of Pi starvation.…”
Section: Discussionmentioning
confidence: 99%
“…When same crop is grown again and again on same piece of land, the autotoxins released through root exudates and from plant debris start accumulate in root zone [23,24]. An increasing number of studies have shown that the accumulation of plant released phenolic compounds due to continuous monocropping and exogenously applied autotoxins can alter the composition of soil microbial communities [25][26][27][28][29] including plant beneficial soil microbial species such as Bacillus spp.…”
Section: Changes In Bacillus Spp Community Abundance and Diversitymentioning
confidence: 99%
“…Consecutive monoculture problem (CMP) happens when one plant is cultivated in the same field year after year, which results in growth decline, crop yield reduction, quality degradation, and disease susceptibility. Previous studies have indicated that the causes of the CMP include soil physicochemical properties deterioration, microbial community structure imbalance, and autotoxicity of root exudates [1][2][3]. Cucumber (Cucumis sativus L.) suffers from a severe consecutive monoculture problem especially under greenhouse cultivation, and the main cause for this CMP in cucumber is the secretion of autotoxins.…”
Section: Introductionmentioning
confidence: 99%